Early-Maturing Sweet Oranges: Research Update on Earlygold, Itaborai, Ruby, and Westin Sweet Oranges - William S. Castle; James J. Ferguson (EDIS)
Earlygold, Itaborai, Ruby, and Westin are new sweet orange selections with varying combinations of exceptional juice color, interesting flavor, or good soluble solids development early in the fruit season. Considering these characteristics, these cultivars have commercial potential as juice oranges and are discussed here. This document is HS920, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: May 2003.